China’s One Belt One Road Initiative as a support of EU’s European Neighborhood Policy - Żukrowska, Katarzyna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The article looks into prospects of closer cooperation between China and the EU in area of the two policies which are launched by the actors in question. Those policies are One Belt One Road (OBOR) and European Neighborhood Policy (ENP). It discusses the two policies and visions which are covered in the two initiatives, what is followed by indicating common elements of the two and differences in interests. The assumption is that the two: China and the EU are engaged in external aid which stimulates growth, nevertheless their initiatives are different and they offer other things to the countries which they concern. Moreover they also can be seen as mutually supplementing each other, rather than competing
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 486, s. 129-140
Keywords: One Belt One Road Initiative; China; Jeden Pas – Jedna Droga; Chiny